2016
DOI: 10.3892/ijmm.2016.2831
|View full text |Cite
|
Sign up to set email alerts
|

Wheat-bran autolytic peptides containing a branched-chain amino acid attenuate non-alcoholic steatohepatitis via the suppression of oxidative stress and the upregulation of AMPK/ACC in high-fat diet-fed mice

Abstract: Abstract. Whole-wheat intake is known to reduce the risk of metabolic syndrome. However, the active component remains unclear. Recently, we identified bioactive peptides [leucinearginine-proline (LRP) and leucine-glutamine-proline (LQP)] from wheat bran autolytic hydrolysate. The present study aimed to investigate the effects of LRP and LQP on non-alcoholic steatohepatitis (NASH) in a mouse model. We also evaluated the effects of these peptides on oxidative stress and on the AMP-activated protein kinase (AMPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Furthermore, the supplementation of BCAAs did not improve the liver dysfunction of ob/ob mice. Previous studies reported the beneficial effects of BCAA on hepatic steatosis in NAFLD/NASH mouse models . The discrepancy might be led by differences in model mice or rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the supplementation of BCAAs did not improve the liver dysfunction of ob/ob mice. Previous studies reported the beneficial effects of BCAA on hepatic steatosis in NAFLD/NASH mouse models . The discrepancy might be led by differences in model mice or rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the beneficial effects of BCAA on hepatic steatosis in NAFLD/NASH mouse models. [34][35][36] The discrepancy might be led by differences in model mice or rats. Leptin-deficient ob/ob mice induced more severe steatosis and liver dysfunction than the diet-induced model.…”
Section: S Trict Evaluation Of the Area Of Lds In Hepato-mentioning
confidence: 99%
“…showed that liver function and glucose metabolisms were ameliorated. However, no biochemical experimentation was performed for liver function and glucose metabolisms such as glucose tolerance test and insulin tolerance test (Kawaguchi et al, 2017). muscle cells (20.4%) that indicates RBE can be a potent candidate in diabetic management (Arun et al, 2020).…”
Section: Bioactive Peptides In Diabetes Managementmentioning
confidence: 99%
“…nas de las capas externa e intermedia son bá-sicamente enzimas que actúan contra el estrés oxidativo y contra patógenos que sobreviven a la deshidratación, enzimas hidrolíticas necesarias para la germinación, así como inhibidores de otras enzimas (Jerkovic y col., 2010;Koehler y Wieser, 2013). Las proteínas de la capa aleurona están constituidas en un 58 % por globulinas, aproximadamente, cuya función principal es la de reserva para su uso durante la germinación; el restante 42 % tiene actividad enzimática (Jerkovic y col., 2010; Meziani y col., 2012).…”
Section: Biotecnología Y Ciencias Agropecuariasunclassified